EFFICACY OF BIOAPIGYN OINTMENT FOR PELVIC MUSCLE TONUS IN THE TREATMENT OF STRESS URINARY INCONTINENCE AND VULVOVAGNAL DISORDERS - Višnja, Oreščanin; Štefica, Findri Guštek; Ivan, Fistonić; Josipa, Rodić (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Objectives: The purpose of this work was development, formulation and testing of new herbal ointment for the treatment of stress urinary incontinence and its related symptoms and comparison of its efficiency with the results of pelvic muscle training. The influence of the treatment or training onto vulvo-vaginal disorders was also determined. Materials and methods: 132 women in the age range from 32 to 77 years were randomly selected into experimental and control group. The experimental group was treated two weeks with Bioapigyn ointment for pelvic muscle tonus (2 g/day) which consisted of the following ingredients: honey; glycerol, Cera flava, oil macerates of the plants Capsella bursa-pastoris, Urtica diodica, Quercus robur, Salvia officinalis, Achillea millefolium, Alchemilla vulgaris, Calendula officinalis, Matricaria chamomilla, Plantago major; essential oils of the plants Melaleuca alternifolia, Thymus vulgaris ct. tymol, Origanum vulgare. Control group was subjected to pelvic muscle training during 24 weeks (three times a week). The degree of incontinence and its impact on the quality of life prior and after the treatment or training was assessed by the International Consultation on Incontinence Questionnaire - Urinary Incontinence Short Form (ICIQ-UI SF), where maximum score of 21 represents permanent incontinence and 0 no leakage of urine. The volume of residual urine, perineometry and vaginal pH were also determined before and after the treatment or training. For statistical evaluation STATISTICA 11.0 package was used. Results: The variables with the highest, statistically significant influence onto degree of incontinence and its impact on the quality of life were body mass index and menopause. Significant decrease following the treatment with Bioapigyn ointment was found for ICIQ-UI SF score (from 12.43±4.83 to 8.61±4.92, p<0.00001), residual urine volume (from 8.73±11.18 to 2.78±5.93 mL, p=0.0002) and vaginal pH (from 6.30±0.63 to 5.59±0.50, p= 0.0000). The increase in the muscle strength was also confirmed. In the end of the treatment all the symptoms of vulvo-vaginal disorders disappeared completely in all 66 participants. Control group also showed some improvement in the values of ICIQ-UI SF score, residual urine and perineometry results. However, those changes were not statistically significant. There was no improvement concerning the vaginal pH and the symptoms of vulvo-vaginal disorders. Conclusion: Preliminary study confirmed the efficiency of Bioapigyn ointment for pelvic muscle tonus in the treatment of stress urinary incontinence as well as the symptoms of vulvo-vaginal disorders due to its components with smooth muscle contraction activity, uterotonic activity as well as pH adjusting, coating, moisturizing and soothing effect. Significantly better results for most of the variables were found in the experimental compared to the control group.